Islamic Javanese Ideas in The Poetry Collection of Air Kata Kata by Sindhunata - Siti - Fatimah; Joko Nurkamto; Budi Setiawan; Ngadiso Ngadiso (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This study aims to describe the views of Islamic Javanese ideas in Sindhunata's poem Air Kata Kata. The Islamic Javanese view is obtained by using the deep interpretation of the symbols in the texts and images/ paintings contained in poems by a Catholic Pastor who has a humanist spirit and is familiar with Islamic Javanese life. Based on this research, the researcher obtained an Islamic Javanese view in Catholic poet’s works who was close to the daily life of Moslems. Therefore, his works are influenced by Islam and the life of Moslems.